External propagators in wasp: Preliminary report - (:unkn) unknown (CEUR-WS, 2016)
State-of-the-art ASP solvers are based on a variant of the CDCL algorithm. One of the key features of CDCL is the propagation step, whose role is to implement deterministic consequences of the input theory. It is well-known that the performance of solvers can be considerably improved on specific benchmarks by adding custom propagation functions. However, embedding a new propagator into an existing solver often requires non-trivial modifications. In this paper, we report on an extension of the ASP solver WASP that allows to provide new propagators externally, i.e. no modifications of the solver are needed. We assess our proposal on a recent application of ASP to abduction in Natural Language Understanding, where plain ASP solvers are not effective. Preliminary experiments on real-world instances show encouraging results.
Keywords: Answer set programming; Natural Language Understanding; Propagators